Emerging insights into the role of visceral adipose tissue in diabetic kidney disease - Li, Linrong; Liu, Cuiping; Gu, Junling (Frontiers in Nutrition, 2025)
Diabetic kidney disease (DKD) is one of the primary microvascular complications of diabetes mellitus and the leading cause of end-stage renal disease. Obesity, which increases the risk of metabolic disorders, plays a crucial role in the onset and progression of DKD. Visceral fat area (VFA), recognized as the gold standard for diagnosing central obesity, can be accurately measured via imaging techniques. Visceral adipose tissue (VAT) regulates disease progression through a variety of potential mechanisms and promotes the occurrence and development of DKD. This review summarizes the assessment methods of VFA, the association between VAT and DKD, and the potential mechanisms by which VAT drives DKD pathogenesis, aiming to provide insights into the role of VAT assessment and its mechanisms in the prevention and treatment of DKD.